If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x+7=16x-43
We move all terms to the left:
12x+7-(16x-43)=0
We get rid of parentheses
12x-16x+43+7=0
We add all the numbers together, and all the variables
-4x+50=0
We move all terms containing x to the left, all other terms to the right
-4x=-50
x=-50/-4
x=12+1/2
| 6=-3r+5r | | 4=-5l+4l | | -10=-q-4q | | 3/x-16=14 | | 21y^=6y | | r(r-10)=10 | | 8.00+.75x=6+1.25x | | 21y-6y^=6y^-6y^ | | 150-35x=35 | | 2/3x+2=18 | | 3/2x-6=8 | | 3(−x−2)+5x−5=-5 | | 2y+13=45 | | 3=9l-6l | | 6=10u-8u | | 8-4x=-2(x-4) | | 7=3u-17 | | x-(-20)=2 | | Y=1.45x+25.98 | | 5+k=-17 | | -21+k=-32 | | a~6+2=10 | | 100c2=9 | | n-27=-8 | | x=(100+x)*0.2 | | 18=5w-2w | | x-(-19)=18 | | 20-5x=-4x-10 | | t/2.7=4.3/6 | | x+(-29)=-49 | | 140=25s+40 | | n-(-12)=4 |